Hubungan antara Efikasi dan Regulasi Diri dengan Motivasi dan Hasil Belajar Kimia Peserta Didik Kelas XI MIA SMAN 8 Gowa pada Materi Pokok Hidrokarbon - Satnur, Muh. Alham; Ramlawati, Ramlawati; Danial, Muhammad; Nisai, Khaerun (Program Pasca Sarjana UNM, 2024)
This study is an ex post facto with a sample of 141 students. The data collection technique consists of questionnaires and test. Based on the results it is known that (1) the level of efficacy and self-regulation of students are in the high category with each percentage of 50.35% and 43.97%; (2) the level of motivation and chemistry learning outcomes of students respectively are in the high category and good with each percentage of 52.06% and 37.59%; (3) there is a positive and significant relationship between efficacy and self-regulation with learning motivation in which the correlation category in a row is perfect and strong; (4) there is a positive and significant relationship between efficacy and self-regulation with learning outcomes in which the correlation category in a row is strong and moderate; (5) there is a simultaneous relationship between efficacy and self-regulation%; and (6) there is a simultaneous relationship between efficacy and self-regulation with the results of bejar learners by 54.7% where each independent variable successively contributed effectively by 39.9% and 14.9%.